PKM WORKSHOP TINKERCAD: MENGHIDUPKAN SAINS DENGAN SIMULASI INTERAKTIF BAGI PESERTA DIDIK MTS DDI LAPEO - Agung, Afiq; Saddia, Andi; Fadhila, Fadhila (Education and Talent Development Center of Indonesia, 2025)
The results of observations and interviews conducted at MTs DDI Lapeo showed that learning at the school was still dominated by one-way lecture methods and was less interactive. The strategies commonly used by teachers did not support the needs of practical-based science, so that students still had few opportunities to interact with learning objects. This community service aims to increase students' interest in science at MTs DDI Lapeo with the help of an interactive simulation called Tinkercad. The implementation method consists of three main stages: preparation, implementation, and evaluation. The preparation stage involves initial observation, document collection, FGD, and team briefing. In the implementation stage, participants were trained to foster interest in science with interactive simulations by raising their learning materials in class. The results of the questionnaire showed that the paper-making workshop received a very positive response, especially from aspects related to the material, and student respondents agreed that this activity actively involved them and greatly increased their interest. The training was considered interactive, not boring, and able to create interesting conditions for participants. No less importantly, this activity gave them satisfaction while participating in the activity.